Prevenção das alterações funcionais e cognitivas do envelhecimento: a influência do exercício e da estimulação cognitiva em dupla tarefa - JARDIM, Naina Yuki Vieira (Universidade Federal do Pará, 2018)
In face of the worldwide aging rate and the silent epidemic cognitive decline and dementia in elderly, the need for intervention strategies to protect and/or improve the functionality and cognitive performance on aging increased. Recent studies suggested that as compared with single stimulation protocols, dual task interventions involving physical exercise and cognitive tasks are more efficient by improving cognitive performance and ability in functional tasks. Although preliminary results in the literature are promising, there are few research using dual-task stimulation protocols. In the present report we aim to investigate the effects of a dual-task intervention program (multimodal physical exercise and multisensory stimulation) on cognitive performances, functionality and quality of life of healthy old adults. To that end 28 community-dwelling old adults (66.14 ± 1.00 years old) underwent cognitive, physical and quality of life assessments at baseline and post-intervention. Cognition was evaluated through Mini Mental State Examination (MMSE) for screening, Semantic and Phonological Verbal Fluency, CERAD word list and automated neuropsychological tests (CANTAB); physical assessments included cardiorespiratory fitness (Six-Minute Walk Test), functional mobility (Timed-up and go Test), muscle strength of lower limbs (30-seconds Chair Stand Test) and upper (dynamometer Jamar®) limbs muscle strength; Dual task functional test were performed by Walking While Talking test and quality of life questionnaire (SF36) were also applied. Subjects participated in dual-task intervention program composed by physical exercise (aerobic and strength training) and multisensory stimuli, composed by 24 sessions, conducted twice a week for 75 minutes each. Outliers values were excluded, and T-test was applied to investigate possible differences between baseline and post-invention assessment. After intervention, subjects showed increased cognitive performance (MMSE, verbal fluency, short-term memory, sustained visual attention, learning, short-term visual recognition memory), better physical and functional parameters (upper limb strength, cardiorespiratory fitness, functional mobility), improved performance in the dual task functional test and personal perception about improved physical function and diminished limitations due to physical problems (SF36). Thus, 24-session dual task intervention program, based on aerobic and strength exercises and multisensory stimulation, improves cognition, functional exercise capacity, quality of life and ability to perform dual task activities, as normally required in the daily routine of the old adults.